The answer is 28y hope this helps
Answer: x = 7
Step-by-step explanation:
4(2x-3) = 6x+2 <--distribute the 4
8x - 12 = 6x + 2 <---add 12 to both sides
8x = 6x + 14 <--- subrtract 6x from both sides
2x = 14 <--- divide by two
x = 7
First, we have to realize that this is factored form, so we have to put this in standard quadratic form using FOIL, which is a rule mandating how we multiply the numbers here. F stands for First, which means the first number inside the parentheses for both of them, then O means the first number in the first quantity(fancy word for parentheses) multiplied by the last number of the second quantity, and so forth. When you are done, you combine like terms
anyway, you end up with x²-12x-189, but you have to inverse all numbers because of the parentheses in front, so it becomes -x²+12x+189.
Now you can find the axis of symmetry uisng the equation -b=2a (oh yeah, I forgot to mention: the standard quadratic form is a(x)²+b(x)+c already). So you do -12 / -2, which then becomes 6.
The axis of symmetry is 6
Quick Answer SSS
Proof
AC = DB
AB = DC
BC = BC This side is equal to itself and is common to both triangles.
Three sides of one triangle equal to 3 sides of the other means that the triangles are congruent. It is the Theorem you need.
Answer: 18.7
Step-by-step explanation:
Find the lengths of AB, BC, and CA
AB =
= 5
≈ 7.1
BC =
= 5
≈ 7.1
CA =
= 2
≈ 4.5
7.1 + 7.1 + 4.5 = 18.7